An assessment of the suitability of contract farming models being implemented in Zimbabwe and their impact on agricultural growth (2010 to December 2014) - Chamahwinya, James (Midlands State University, 2017)
This study was carried in wake of the challenges bedevilling the once lucrative contract farming business where a number of contract farming funders withdrew their arrangements citing side marketing, failure to repay loans while farmers complain about prices offered by funders which are too low for sustainability. It is to be established if the increase in the level of tobacco production is commensurate with beneficiation of both contracting parties. The purpose of this is to assess the suitability of contracting farming models being implemented in Zimbabwe and their impact on agricultural production. The study sought to assess the contract farming models, determine the experience and level of education of farmers, the farmers’ understanding of the legal basis of contract farming, to explore conducive conditions for successful contract farming and assess the impact of those models to agricultural production. In this study a population of three thousand contract farmers was used, a sample of one hundred tobacco farmers from Hurungwe district was selected using purposive sampling. Data was collected using self-administered questionnaires and face to face interviews. The collected data was collated and analysed using SPSS and was presented in tables, graphs and charts. The key findings of the study were that contract farming models are not suiting the farmers needs although contract faming has opened new markets for farmers. There are limited contract farming models available to farmers and this has created a monopoly to funders. Farmers are not being involved in the drafting of the contracts to which they will sign. Farmers are experiencing challenges which centre on the way the contracts are drawn and there are untapped opportunities from tobacco contract farming. The researcher recommends that Government of Zimbabwe should play an active role in the management of these contracts to protect farmers. More funders should be registered to break monopoly and farmers should be given choices of models to choose from.